The Philological and communication studies at the beginning of the XXI century: heritage and prospects. On the 80th anniversary of the birth of the first editor of the journal "Philology & Human" Alexey Andreevich Chuvakin - Chernyshova, Tatiana (Philology & Human, 2021)
Material for the anniversary of A.A. Chuvakin. Column editor